Exploring Passenger Concerns And Challenges In Using Digital Transportation Ticket Booking Platforms - V. Gopalakrishnan, V. Gopalakrishnan; Sathish, M. Thangajesu; A. Venkatesan, A. Venkatesan (Journal of Neonatal Surgery, 2025)
The rapid digitalization of the transportation sector has transformed the ticket booking process through the introduction of online and mobile-based platforms, offering passengers greater convenience, accessibility, and time efficiency. Despite these advantages, users continue to encounter several challenges while using digital transportation ticket booking systems. The present study aims to explore the concerns and challenges faced by passengers in using digital transportation ticket booking platforms in Thoothukudi District. The study adopts a descriptive and analytical research design and is based on primary data collected from 260 respondents using a structured questionnaire through the Convenience Sampling method. The collected data were analyzed using Independent Sample t-test, and One-Way ANOVA to examine the relationship between demographic variables and the challenges experienced by users. The findings reveal that passengers face issues such as technical problems, payment security concerns, software usability, lack of digital facilities, and operational difficulties while booking tickets online. Significant differences were observed for selected challenges across demographic groups, whereas many challenges were found to be common irrespective of gender, age, area of residence, and income. The study highlights the need for improving digital infrastructure, user-friendly interfaces, secure payment mechanisms, and customer support services to enhance user satisfaction and encourage wider adoption of digital ticket booking platforms....